Dialog Islam-Budaya: Merumuskan Sikap Islam Atas Budaya Lokal - Khaerul Paizin (Al Irfani: Journal of Al Qur'anic and Tafsir, 2021)
This study aims to examine the interaction of Islam and Arab culture; in this case, the response of the Prophet saw with the culture of the Arab community. As uswah hasanah for his ummah, the variety of responses of Rasulullah saw contained in the hadith and historical records will be identified and then lessons will be taken from it. The background of this paper stems from the anthropological fact that society, including the Arab society before the advent of Islam, is not a society empty of culture or sterile from the influence of religion, customs, morals, and rules of life that have existed among them. As soon as Islam came with all the norms that were in it, then Islam interacted with it and became a filter for the culture, customs, and beliefs that already existed among the pre -Islamic Arab society. The question is how did Muhammad saw respond to that tradition? This study is based on a study of historical literature that contains the Prophet's response to the traditions of the Arab community. There are four important findings that can be noted regarding the Prophet's response to the jāhiliyyah tradition. First, the tradition is fully accommodated (total accommodation). Second, traditions that are totally rejected or totally corrected (total refuse or total correction). Third, traditions that are partly adopted but partly rejected (particular accommodation). Fourth, the tradition is in principle preserved with a little modification here and there (synchronization and modification).